Communication improvements and gas danger analysis used for the CAESAR robot. (26th January 2011) - Stopforth, Riaan; Bright, Glen; Harley, Ronald
Urban search and rescue robots are required for the searching of victims in disaster scenarios. Some of the problems experienced before were involved reliable communication with the robot and unsafe environmental conditions, which are harmful to the rescuers. The improvements conducted as used for the contractible arms elevating search and rescue robot are explained and discussed. These involve frequency selection, protocols, antenna design and models for gas danger decisions.